(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In the same way every circle is corresponding to an equal sided triangle the 3-sphere is corresponding to an inserted tetraeder. The latitude of the corners of the tetraeder on the 3-sphere is calculated here giving the result arcsin(1/3), while arcsin(1/2) is derived for the 2-dimensional sphere.